Cellular concept learning package / Noor Aishah Muslim - Muslim, Noor Aishah (2007)
In this project a learning package system is developed under Matlab using Graphical User Interface (GUI). It is an executable system which is specially designed to construct the instructor task easier in teaching the electrical communication engineering concepts and to assist students in getting a clearer understanding of Cellular Concept. The Cellular Concept Learning Package software consist of three parts which are notes, examples and simulation. It exists to enable users to learn more topics in cellular concept such as cell pattern, frequency reuse and traffic intensity. The learning package allows bringing students up to speed with concepts and quickly finding information. It will be clearly designed to provide the best learning opportunities. Students will find the benefits of use the package, as it provides the ability to learn from scratch or just look up a tag. This package provides accurate solutions and enables precise, compact and clear documentation of the models along with the results with minimal effort on the part of the user. At the end of the project, users are able to view their notes by using this software. The project mainly focuses on the accessibility to a Cellular Concept topic. This simply means that a user can be anywhere in learning process.